2020
DOI: 10.21203/rs.3.rs-73143/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PD-L1 expression in liver metastasis: its clinical significance and discordance with primary tumor in colorectal cancer

Abstract: Background: The outcomes of immune checkpoint inhibitors of patients with cancer liver metastases are poor, which may be related to a different tumor microenvironment from primary cancers. This study was aimed to analyze the PD-L1 expression and the immune microenvironment status in liver metastatic diseases and compare the differences of PD-L1 expression between primary tumors and liver metastases of colorectal cancer.Methods: 74 cases of pathologically confirmed colorectal cancer liver metastasis underwent r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…However, this mechanism is utilized by cancers to escape from anti-tumor immunity. Previous study showed that the expression of PD-L1 was increased in liver metastases compared to primary CRC, indicating different intrinsic microenvironment between primary and metastatic CRC [110], which may help CRC liver metastases escape from immune surveillance. In addition, it was reported that chemotherapy can modulate PD-L1 and TIM-3 expression in CRC liver metastases, suggesting the potential strategy of combined chemo-immunotherapies [111].…”
Section: Immune Checkpoint Moleculesmentioning
confidence: 98%
“…However, this mechanism is utilized by cancers to escape from anti-tumor immunity. Previous study showed that the expression of PD-L1 was increased in liver metastases compared to primary CRC, indicating different intrinsic microenvironment between primary and metastatic CRC [110], which may help CRC liver metastases escape from immune surveillance. In addition, it was reported that chemotherapy can modulate PD-L1 and TIM-3 expression in CRC liver metastases, suggesting the potential strategy of combined chemo-immunotherapies [111].…”
Section: Immune Checkpoint Moleculesmentioning
confidence: 98%
“…Wei et al. found that the levels of PD-L1 in liver metastases were higher compared with primary tumors ( 10 ). The immune escape of the tumors was reversed by immune checkpoint inhibitors, novel drugs developed to block these negative feedback pathways by binding to PD-1 (nivolumab, pembrolizumab), PD-L1 (atezolizumab), CTLA-4 (ipilimumab).…”
Section: Rationale For Immunotherapy In Mcrcmentioning
confidence: 99%